If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -7 = 9 + 2 Reorder the terms: -7 + 10y = 9 + 2 Combine like terms: 9 + 2 = 11 -7 + 10y = 11 Solving -7 + 10y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 10y = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 10y = 11 + 7 10y = 11 + 7 Combine like terms: 11 + 7 = 18 10y = 18 Divide each side by '10'. y = 1.8 Simplifying y = 1.8
| 4(a-1)=76 | | 5x-8=6+8x+4x | | 162=x+142+x+44 | | 45=16t+23-9t | | p+4=9.5 | | 2x-18=3x-9 | | (5x+20)+(4x-2)=180 | | (u+3)*9=39 | | =12n-100 | | 12p-18-5p+38= | | (q-4)*6=18 | | 7y=-20 | | -1(x+14)=(-24) | | 2x+10t=0 | | 8u+24= | | 4(m-2)=-2(m-5) | | -5(1-5x)+5(8-8x-2)=-4x-8x | | 3y-15=-4y-4 | | =5x+3 | | x-2=-6x-8 | | 15x^2-5x-2=0 | | Y=35+0.8x | | 7(4x+1)=28x-4 | | 10x-(3x-8)=36 | | 67.2=5-18.6 | | y-3x=12+3x | | 2ln(4x)=15 | | x-4=-4x-5 | | 6x^2+7=-42 | | x-4=4x+5 | | 5z=13-33 | | 6.78j-5.2=4.3j+2.15 |